Bad Kitty for President - Bruel, Nick (New York : Roaring Brook Press, 2012)
Kitty decides to run for President of the Neighborhood Cat Association.
"A Neal Porter Book."
Keywords: Cats -- Juvenile fiction; Politics, Practical -- Juvenile fiction; Elections -- Juvenile fiction